Autocad 2007 for architecture - Jefferis, Alan; Jefferis, Tereasa (Clifton Park, NY : Thomson Delmar Learning, 2007)
Beginning with an exploration of the basic tools that control AutoCAD, each subsequent chapter builds on the skills learned for a well-rounded exploration of each new command relating to 2D construction documentation. All the need-to-know information that current and future architects, engineers, and designers require is provided, affording readers the efficiencies and skills they need to apply AutoCAD 2007, and its improved application in the architectural and construction fields, using the previous release as its base in their professional environment. The book is an excellent resource for new users wishing to explore the computer skills needed to excel in the creation of drawings for architectural design, as well as for experienced CAD users adjusting to the new features and functions of AutoCAD 2007.Beginning with an exploration of the basic tools that control AutoCAD
this text provides all the information users need toknow, affording readers the efficiencies and skills they need to apply AutoCAD 2007, and its improved application in the architectural and construction fields, using the previous release as its base in their professional environment.This resource is for new or experienced users and includes information on AutoCAD commands, tables, tool palette, hatch capabilities, M-Text, common 2D commands and the Sheet Set Manager. Also covers new National CAD Standards.Alan Jefferis has been a drafting instructor at Clackamas Community College for more than 27 years. His professional experience includes 8 years of drafting experience with structural engineers, and 23 years as a professional building designer. He is currently the owner of Residential Designs, and is co-author of numerous books from Thomson Delmar Learning, including Architectural Drafting and Design
Print Reading for Architectural and Construction Technology, Commercial Drafting and Detailing, AutoCAD 2002 and AutoCAD2002 and the Fundamentals of Mechanical Drafting.Michael Jones is the CAD Systems Manager, Department Chairperson, and a CAD instructor at Clackamas Community College, which is an Autodesk Premier Training Center in Oregon City, Oregon. Mike has introduced new users and experienced professionals to the commands and options of AutoCAD for over 23 years. His training center experience is enhanced by 25 years of professional drafting and CAD system management experience in private industry.Tereasa Jefferis is a graduate of Clackamas Community College and the Mechanical Systems Institute. She has been an architectural drafter for nine years and has experience in architectural drafting, commercial plumbing drawings, and with HVAC system design. She designed several of the homes that are shown throughout this text. She currently works as an independent contractor with multiple mechanical engineer firms.
Exploring Autocad Tools And Displays -- Creating Drawing Aids -- Drawing And Controlling Lines -- Working With Drawing Files -- Drawing Organization -- Drawing Geometric Shapes -- Controlling Drawing Accuracy -- Drawing Display Options Basic Methods Of Selecting And Modifying Drawing Objects -- Modifying The Position And Size Of Drawing Objects -- Polylines Supplemental Drawing Commands -- Placing Patterns In Drawing Objects -- Inquiry Commands -- Placing Text On A Drawing -- Introduction To Dimensions -- Placing Dimensions On Drawings -- Adding Attributes To Enhance Blocks -- Oblique And Isometric Drawings -- Working With Multiple Drawings -- Combining Drawings Using Xref -- Working With Layouts And Viewports -- Working With Sheet Sets -- Controlling Output -- Autocad And The Internet.
Includes index.
1
Keywords: CIT; AutoCAD; CEM; Architecture -- Computer-aided design; Architectural drawing -- Data processing